2021
DOI: 10.3390/coatings11111341
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Influence of Different Rotations of Organic Formamidinium Molecule on Electronic and Optical Properties of FAPbBr3 Perovskite

Abstract: Hybrid organic–inorganic halide perovskites (HOIPs) have recently represented a material breakthrough for optoelectronic applications. Obviously, studying the interactions between the central organic cation and the Pb-X inorganic octahedral could provide a better understanding of HOIPs. In this work, we used a first-principles theoretical study to investigate the effect of different orientations of central formamidinium cation (FA+) on the electronic and optical properties of FAPbBr3 hybrid perovskite. In orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 106 publications
0
11
0
Order By: Relevance
“…MAPbI 3 displays a common sequence of tilted phases observed by multiple researchers; the high-temperature parent uptilted cubic phase, Glazer notation: a 0 a 0 a 0 , distorts upon cooling to a tetragonal phase with one in-phase rotation ( a 0 a 0 c + ) and eventually to a ubiquitous orthorhombic low-temperature structure with both in-phase and out-of-phase rotations ( a – b + a – ). , This Glazer’s tilting is similar to the OLHPs independent of A-site cations. , The hydrogen attached to the nitrogen (H–N) comes closer and creates hydrogen bonding to the Br atom due to the MA orientation inside the octahedra and stabilizes the octahedral tilting. Also, the fine balance of orbital interactions between the inorganic species determines the degree of octahedral tilting . With the decrease in temperature until the tetragonal regime, the inorganic PbBr 6 octahedra experience a similar kind of Glazer tilt perpendicular to the axial direction (see Figure h).…”
Section: Resultsmentioning
confidence: 80%
“…MAPbI 3 displays a common sequence of tilted phases observed by multiple researchers; the high-temperature parent uptilted cubic phase, Glazer notation: a 0 a 0 a 0 , distorts upon cooling to a tetragonal phase with one in-phase rotation ( a 0 a 0 c + ) and eventually to a ubiquitous orthorhombic low-temperature structure with both in-phase and out-of-phase rotations ( a – b + a – ). , This Glazer’s tilting is similar to the OLHPs independent of A-site cations. , The hydrogen attached to the nitrogen (H–N) comes closer and creates hydrogen bonding to the Br atom due to the MA orientation inside the octahedra and stabilizes the octahedral tilting. Also, the fine balance of orbital interactions between the inorganic species determines the degree of octahedral tilting . With the decrease in temperature until the tetragonal regime, the inorganic PbBr 6 octahedra experience a similar kind of Glazer tilt perpendicular to the axial direction (see Figure h).…”
Section: Resultsmentioning
confidence: 80%
“…which is proportional to the inverse of ( ) e w 2 of DF can be calculated with the following equation [109,111]. The ( ) w J o function relates to optical transitions caused by photon energy (w).…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Experimental analysis has indicated that the thermophysical factors of the water-CMC solution for volume fraction less than 6% is similar to water and thermophysical of titanium oxide (TiO2) are shown in Table 1 [48]. Density and specific heat of non-Newtonian nano-fluid are calculated as follows [49]:…”
Section: Thermophysical and Rheologicalmentioning
confidence: 99%